EPIDEMIOLOGY OF CHILDHOOD FRACTURES IN THE CITY OF KARACHI - Mansoor, Kanaan; Shahnawaz, Saba; Ahmad, Ali; Arif, Muhammad Mustafa; Hamza, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: The epidemiology of paediatric fractures is crucial for developing preventive strategies, but when it comes to developing countries, the urban scenario has rarely been studied in the context of childhood trauma. This study aims to identify the epidemiology of paediatric injuries occurring in the largest and most populated city of Pakistan, Karachi, so that a comparison to data from the developed world can be made, and appropriate precautionary measures can be devised. Methods: The data from 1,514 paediatric orthopaedic patients treated at the Accident and Emergency department of Jinnah Postgraduate Medical Centre, during the time frame ranging from January 2012 to January 2013 was studied. Survey forms were filled out by the residents on call. Results: The patients’ ages ranged from 2 months to 17 years, with males outnumbering females. The mean age of presentation was 8.8±4.6years. The number of fractures was maximal among children aged 5-11 years, after which it decreased in adolescents. Fractures of the radius and ulna were most common (16.9%), followed by the distal radius (14.6%) and humerus (12.0%). Patients aged 0-2 years most commonly presented with a fracture of the femoral shaft. Falls on the same plane were responsible for the most fractures (44.2%), followed by falls from a height (21.5%) and road traffic accidents(26.7%).Incidence of fractures peaked in the summer months (p=0.007). Conclusion: Adequate precautionary measures and preventive programs need to be inculcated through legislation and a community based effort. In a developing nation however, unless the issues of ignorance, illiteracy and poverty are tackled by the authorities, they will continue to be a major hindrance.